سیرت ِ محمدی سے متعلق مغربی نظریات: عہدِ ِنشاۃِ ثانیہ کا مطالعہ: Western Theories on Muhammad’s Personality: A study of the Age of Renaissance - Dr. Saima Munir; Dr. Naseem Akhter; Dr. Muhammad Iqbal (Al-Qamar, 2020)
From a long history of Sīrah scholarship in the West, this paper explores the relevant studies that came to light during the age of Renaissance. It demonstrates that the general atmosphere in this period was similar to that of the middle ages in terms of western metaphors on the personality and character of the Prophet. In the general superstitious environment of the referred era, however, some voices are heard condemning the West’s prejudices against Prophet Muhammad peace be upon him. For example, the seventeenth-century writer Henry Stubbe condemned many of the awkward Western ideas and praised the character of the Prophet of Islam. But this kind of examples are exceptional, the general mood of the time was biased and prejudiced.